The Effect of Service Quality, Trust, and Corporate Image on Passenger Satisfaction of the Bawean Island Ferry Operated under the Port Authority and Harbormaster Office (KSOP) Class II Gresik - Malik, Djamaludin; Purwiyanto, Ddik; Wiedodo, Wisnu (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study aims to analyze the influence of service quality, trust, and corporate image on customer satisfaction of the Bawean Island ferry service managed by the Port Authority and Harbormaster Office (KSOP) Class II Gresik. Using a quantitative approach with survey methods, primary data was obtained from 100 respondents of KM Express Bahari 3F and KM Express Bahari 6F passengers. The data were analyzed using multiple linear regression with SPSS. The results indicate that service quality and corporate image significantly affect customer satisfaction, while trust does not have a significant effect. Corporate image is the most dominant variable. Simultaneously, the three variables significantly affect customer satisfaction with an Adjusted R² of 0.742. This means that 74.2% of the variation in customer satisfaction can be explained by service quality, trust, and corporate image. The findings imply that service quality and a strong corporate image are essential for enhancing customer satisfaction, while trust needs to be strengthened through transparent communication and consistent operational reliability.